Simulation of the song motor pathway in birds: A single neuron initiates a chain of events that produces birdsong with realistic spectra properties (2018)
ABSTRACT: Birdsong is a complex learned behavior regulated by Neuromuscular coordination of different muscle sets necessary for producing relevant sounds. We developed a heterogeneous and stochastically connected neural network representing the pathway from the high vocal center (HVC) to the robust nucleus of the arcopallium (RA) neurons that drive the muscles to generate sounds. We show that a single active neuron is sufficient to initiate a chain of spiking events that results to excite the entire network system. The network could synthesize realistic bird sounds spectra, with spontaneous generation of intermittent sound bursts typical of birdsong (song syllables). This study confirms experiments on animals and on humans, where results have shown that single neurons are responsible for the activation of complex behavior or are associated with high-level perception events.